EXPLORING STUDENT’S PERCEPTION OF ONLINE LEARNING FOR PUBLIC SPEAKING COURSE ( A CASE STUDY AT KIND ENGLISH COURSE PARE KEDIRI ): Studi Kasus di KIND ENGLISH COURSE PARE KEDIRI - Mega Kristina (Prosiding SNasPPM, 2021)
Public speaking is one of the skills that must be mastered by students. Speaking is a communication skill that is essential for intellectual development, career trajectory, and civic engagement. Public speaking is universally applicable to all types of majors and occupations, but with the current state of the pandemic Covid-19, students have difficulty learning to develop public speaking. Based on the problems above, students are looking for ways to learn public speaking skills by taking online courses in Pare Kediri. After taking online classes in Pare Kediri, students were asked to fill out a questionnaire on student perceptions about the results of online class learning and what difficulties they encountered during online learning. Students' perceptions can later be used as evaluation material for course institutions to be better in dealing with online classes during the pandemic Covid -19. This research uses qualitative methods. where data collection is obtained from observations, filling out questionnaires and interviews with students. Data collection was carried out to determine students' perceptions of online public speaking learning and the difficulties faced during online classes at Kind English Courses during the pandemic Covid19. The results of this study indicate that students' perceptions of online learning at Kind English Courses during the pandemic Covid-19 are very effective and help students in public speaking, students feel able to study at home and do not have to go to Kampung Inggris Pare Kediri. Students also stated that even though they attended online class students also felt their speaking abilities increased from before and they also felt more confident. Although online learning is said to be effective students also have difficulties in online classes, students do not interact with the tutors and other students, due to public speaking learning, many people need to train more trust in speaking, besides that students are sometimes constrained by signal problems that sometimes break up so that the material explained by the tutor cannot sound so clear.